2019
DOI: 10.1021/acs.langmuir.9b00918
|View full text |Cite
|
Sign up to set email alerts
|

Brush Swelling and Attachment Strength of Barnacle Adhesion Protein on Zwitterionic Polymer Films as a Function of Macromolecular Structure

Abstract: The exceptional hydration of sulfobetaine polymer brushes and their resistance toward nonspecific protein absorption allows for the construction of thin films with excellent antibiofouling properties. In this work, swollen sulfobetaine brushes, prepared by surface-initiated atom transfer radical polymerization of two monomers, differentiated by the nature of the polymerizable group, are studied and compared by a liquid-cell atomic force microscopy technique and spectroscopic ellipsometry. Colloidal AFM-based f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Comparison of the nanomechanical and adhesive properties in water, salt water, and deuterium water revealed that the methacrylamide-based films have lower adhesion forces to surfaces, due to the stronger hydration of these brushes in the high-ionic-strength media. 163…”
Section: Solvation and Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the nanomechanical and adhesive properties in water, salt water, and deuterium water revealed that the methacrylamide-based films have lower adhesion forces to surfaces, due to the stronger hydration of these brushes in the high-ionic-strength media. 163…”
Section: Solvation and Swellingmentioning
confidence: 99%
“…A recent paper in this area utilized colloidal AFM‐based force spectroscopy to investigate the response of methacrylamide‐ and styrene‐based sulfobetaine polymer brushes, PSBMAm and PSBVB, respectively. Comparison of the nanomechanical and adhesive properties in water, salt water, and deuterium water revealed that the methacrylamide‐based films have lower adhesion forces to surfaces, due to the stronger hydration of these brushes in the high‐ionic‐strength media 163 …”
Section: Polymer Applicationsmentioning
confidence: 99%
“…The zeta potential of PS/PSB exhibited a strong negative charge, which should be ascribed to the incorporation of sulfobetaine comonomer. Even with the charge neutrality of the zwitterionic surface, a negative potential is typically observed with an ionic charge of a sulfonate group of zwitterion functionality and corresponding (co)­polymers. ,, Moreover, sulfobetaine-functionalized particles allowed better electrostatic repulsion between charged particles and facilitated the stabilization in solution without the addition of any additives. Thus, the zeta potential measurement was also attributed to the zwitterionic functionalized PS latex.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, a similar finding has not yet been reported. It is well known that polySBMA is not soluble in water [8], where only marginal swelling has been observed, but some degree of loosening of the inter/intra chain network has been reported for NaCl solutions, particularly at low NaCl concentrations, i.e., <0.5 M [22][23][24][25], essentially due to the binding of the salt ions to zwitterions, thus weakening the electrostatic intra/inter-zwitterionic chain attraction forces. This results in strong swelling and consequently in a strong hydration of the polymer.…”
Section: Nanomechanical Adhesion Strengthmentioning
confidence: 99%